The Gender Wage Gap : - among Swedish municipalities - Rickardsson, Jonna; Göthberg, Josefine (Högskolan i Jönköping, IHH, Economics, Finance and Statistics, 2015)
Though successively decreasing over time, gender wage gaps are still large in all western countries. When gender wage gaps exist, there is an unequal distribution of economic power between men and women. This paper examines variables that significantly relate to the differences in the size of the gender wage gap across Swedish municipalities. With data gathered from Statistics Sweden and the Swedish Social Insurance Agency for the year 2011, a series of OLS regressions are performed. By examining what variables are statistically related to variations in the gender wage gap over municipalities, for example, average wage, human capital, gender segregation and work absence, the aim is to further contribute to the field of gender economics. The results in this paper show that the gender wage gap exists in all 290 Swedish municipalities. It varies greatly with women earning only 56 percent of men’s wages in Danderyd to women earning 87 percent of men’s wages in Haparanda. In municipalities where average wages are high the gender wage gap is large. Long-term illness and lowered capacity to work are strong factors negatively affecting the gender wage gap. In municipalities where women are more affected by long-term illness and lowered capacity to work than men the gender wage gap is larger. Furthermore, there is a significant relation between the gender wage gap and human capital. The gender wage gap is larger in municipalities where a large share of the population has a higher education.